Polymorphisms in the interleukin-10 gene cluster are possibly involved in the increased risk for major depressive disorder - Maron Eduard; Eller Triin; Koido Kati; Traks Tanel; Kingo Külli; Vasar Veiko; Vasar Eero; Kõks Sulev (BMC, 2008)
Abstract Background Innate immune inflammatory response is suggested to have a role in the pathogenesis of major depressive disorder (MDD). Interleukin (IL)-10 family cytokines IL-10, IL-19, IL-20, and IL-24 are all implicated in the inflammatory processes and polymorphisms in respective genes have been associated with various immunopathological conditions. This study was carried out to investigate whether single-nucleotide polymorphisms (SNPs) in these genes are also associated with MDD. Methods Case-control association study was performed with seven SNPs from the IL10 gene cluster. 153 patients with MDD and 277 healthy control individuals were recruited. Results None of the selected SNPs were individually associated with MDD. The linkage disequilibrium (LD) analysis indicated the existence of two recombination sites in the IL10 gene cluster, thus confirming the formerly established LD pattern of this genomic region. This also created two haplotype blocks, both consisting of three SNPs. Additionally, the haplotype analysis detected a significantly higher frequency of block 2 (IL20 and IL24 genes) haplotype TGC in the patients group compared to healthy control individuals (P = 0.0097). Conclusion Our study established increased risk for MDD related to the IL20 and IL24 haplotype and suggests that cytokines may contribute to the pathogenesis of MDD. Since none of the block 2 SNPs were individually associated with MDD, it is possible that other polymorphisms linked to them contribute to the disease susceptibility. Future studies are needed to confirm the results and to find the possible functional explanation.